Background and basic features of Ohrid belvica Salmo ohridanus (Steindachner, 1892) of Ohrid Lake - Belichovska Katerina, Belichovska Daniela (Institute of Knowledge Menagament, Skopje, 2016)
Ohrid belvica (Salmo ohridanus, Steindachner, 1892) as one of the representatives of "living fossils" represents tertiary relict and endemic trout species belonging to macrostom salmonids and lives only in Ohrid Lake. It is a small endemic trout which represents expressively a lake and depth type of fish. It feeds mainly on zooplankton, and benthic fauna elements. Historical data for the study of Ohrid belvica, its systematic background, basic features and data on the fish quantity caught in the past are presented.
Keywords: Salmo ohridanus, historical overview, general characteristics